APPENDICEAL TIE SYNDROME: A RARE CAUSE OF SMALL BOWEL OBSTRUCTION - Habib, Rohan; Zainab Zaib; Muhammad Waqas Afzal; Rameesha Habib; Maha Wasim; Muhammad Nauman Shah Afridi (Journal of Ayub Medical College Abbottabad, 2023)
Acute appendicitis and intestinal obstruction are two common surgical emergencies. Acute appendicitis as a cause of closed-loop bowel obstruction is a rare surgical entity. The first case was reported in 1901 and since then only a few cases have been reported. We report an unusual case of a 25-year-old female who presented with the clinical picture of acute small bowel obstruction and was found to have an appendicular knot intraoperatively, through which a small bowel was herniating. The patient was managed via a midline laparotomy and appendectomy.